Non-technological innovations: market performance of exporting firms in South American emerging economies - Pino, César (2015)
Innovation plays a key role in the economic growth of companies, sectors and countries. Even though there is great interest in researching innovation, there is little evidence on the influence of innovation on the performance of exporting firms in emerging economies. This study aims to analyze the effects of non-technological innovations (organizational and marketing innovations) on the market performance of exporting firms. We collected data from firms in fast growing South American emerging economies: Colombia, Peru and Chile, with a final sample of 299 completed surveys. Hypotheses were tested with Structural Equation Modeling (SEM). Our results show that organizational innovations (new or improved organizational methods) have more influence on market performance than marketing innovations. Findings confirm the importance of innovative performance as a mediator between organizational innovations and market performance. Our study contributes to the strategic innovation management field, the design of public policy and the strategy of exporting firms.